Physical exercise as a tool for active aging: A theoretical reflection (Research, Society and Development, 2021)
Objective: to describe the importance of physical exercise in active aging, from a theoretical reflection. Methodology: This is a theoretical essay of a reflective nature of the literature on the practice of physical exercise by the elderly, through a non-systematic bibliographic review on the theme “physical exercise and health of the elderly”, and also through the perception of the authors about the theme. As a search strategy, electronic databases, virtual libraries were defined, respectively the Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE) and Scientific Electronic Library Online (SCIELO), using the descriptors standardized by the Health Sciences Descriptors (Decs): Physical Exercise; Elderly Health; Healthy Aging, and its English counterparts. The survey was limited to articles published in Portuguese, English and Spanish, published in the period from 2010 to 2020, available in full and whose results cover the topic of this research. Result: The analysis of the literature was arranged in three sub-themes: Nuances of aging; Active aging: ways to live well; and Physical exercise in old age. Conclusion: Physical exercise positively impacts active aging, contributing to the improvement in cognitive and functional abilities, reducing the risk of chronic and disabling diseases, increasing quality of life and well-being, in addition to being responsible for the person's insertion elderly in social environments. However, there are gaps regarding the safe execution for each type of physical exercise and the possible health risks related to adverse events such as musculoskeletal injury, muscle fatigue and cardiovascular complications, since the development of such practices must be carried out in a unique way, meeting the individual demand of each person.